Konsep Pendidikan Menurut Islam - Muwahidah Nurhasanah (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2020)
Islam offers a conceptualization of education, which is based on the knowledge of naqliyah which underlies all aqliyah knowledge, so it is hoped that it can integrate reason and revelation, syar'iyyah sciences and ghairu syar'iyyah sciences in the educational process. So, through these efforts can realize the process of humanizing humans as the goal of education, namely teaching, nurturing, training, directing, fostering and developing all the potential of students in order to prepare them to realize their human functions and treatises before Allah SWT, namely to fully serve Allah SWT. and carry out the mission of the caliphate on earth, as a creature that seeks to implement divine values ​​by prospering life in a safe, peaceful and prosperous life together.